Propuesta de políticas de seguridad informática de acuerdo a las ISO 27001 en el gobierno autónomo descentralizado del cantón Pangua. - Cruz Caiza, Carla Cristina (2020)
The present research project analyzed security controls absence and procedures managed by TICs of Municipal Decentralized Autonomous Government of Pangua, thus proceeding to collect information through investigative instruments, such as interview that was conducted with computer system manager obtaining information about certain absences, similarly finding certain anomalies by procedures observing, for this reason it was decided to support with bibliographic sources about companies that implemented computer security policies through ISO 27001 and results, generated a diverse model of policies that meets ISO standards in addition to meet GAD'S needs to implement them in the future. As a result of the research, a proposal was generated for its management documents implementation in order to direct, evaluate and protect TICs, these computer security policies should also assume to implement them by members of Computer Systems Department supported by the other units of the municipality, in order to minimize threats and risks of data loss or to be victims of cyberattacks. In addition allowed organization's management to have a necessary vision to define methodologies of continuous improvement that contributes to optimal fulfillment of institution objectives and services.